Assessment of genetic diversity in garcinia species using peroxidase, RAPD and gene sequence specific amplification polymorphism (GSSAP) - Wittayawannakul, Wacharee (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2010)
The genetic diversity of 22 accessions of the genus Garcinia was assessed using peroxidase, RAPD markers and gene sequence specific amplification polymorphism (GSSAP). Among the 15 isozymes tested, only peroxidase produced reproducible, polymorphic bands with a polymorphism information content (PIC) of 0.79. A total of eight bands were generated forming three fingerprint patterns distinct for G. mangostana, G. binucao, G. kydia and G. lateriflora. No bands were observed for G. livingstonei and G. xanthochymus. The three RAPD primers showed high PIC of 0.92 (OPB-04), 0.78 (OPB-06) and 0.91 (OPB-07). For GSSAP markers, two sets of primers based on the conserved regions of acyl-ACP thioesterase (ACYL-ACP), and chalcone synthase (CHALCS) had relative PICs of 0.75 and 0.89 for ACYL-ACP and CHALCS, respectively. The high PICs indicate the capability of these techniques to quantify genetic diversity in Garcinia species. The dendrograms using UPGMA-SAHN cluster analysis based on peroxidase, RAPD and GSS amplification polymorphism showed that Garcinia species clustered into five groups at mean similarity coefficient 0.54. Group I consisted of all 17 G. mangostana accessions and was further classified into three subgroups (Ia, Ib and Ic). Group II composed of G. kydia and G. lateriflora showed a genetic similarity of 0.94. G. livingstonei, G. xanthochymus and G. binucao were unique in their groups. This study showed that the G. mangostana accessions analyzed had low genetic variation and that the different species can be clearly distinguished by combined peroxidase, RAPD and gene sequence specific amplification polymorphism.